(untitled) - Gamble, John (New York, 2010)
Essentials of Strategic Management responds head-on to the growing requests by business faculty for a concisely-written strategic management text that’s robust and theory-driven and supported with a compelling collection of cases. This text was written with four objectives in mind: Although relatively brief in length, the text provides students with an up-to-date and thorough understanding of essential strategic management concepts and analytic tools. It simplifies the task of demonstrating student learning through course embedded assessment; 3) The concepts are supported by contemporary, well-written cases involving headline strategic issues; and lastly, 4) The text serves as the theoretical foundation of a teaching approach incorporating a business strategy simulation.
Keywords: Business planning,Strategic planning,Hoạch định chiến lược,Kế hoạch kinh doanh